2001
DOI: 10.1176/appi.ajp.158.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Female Psychiatrists

Abstract: Female psychiatrists significantly differ from other female physicians with regard to a number of personal and professional dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
3
12
0
1
Order By: Relevance
“…Our findings are in agreement with earlier mainly cross-sectional studies focused on specialized physicians, as they show higher rates of self-reported burnout, mental disorders, and smoking among psychiatrists when compared to other physicians (3)(4)(5)(6)(7)(8)(9)(10), and studies showing more favorable health behaviors among surgeons and pediatricians (7)(8)(9)(10)(11)(12). We found that the differences between specialties in our study with the majority of participants being nurses were quite similar to those reported for physicians.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in agreement with earlier mainly cross-sectional studies focused on specialized physicians, as they show higher rates of self-reported burnout, mental disorders, and smoking among psychiatrists when compared to other physicians (3)(4)(5)(6)(7)(8)(9)(10), and studies showing more favorable health behaviors among surgeons and pediatricians (7)(8)(9)(10)(11)(12). We found that the differences between specialties in our study with the majority of participants being nurses were quite similar to those reported for physicians.…”
Section: Discussionsupporting
confidence: 92%
“…In hospital settings, there is some evidence to suggest differences in health and health behaviors between staff working in different specialties (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Studies of physicians show elevated rates of "burnout", mental disorders, substance use, and suicide among psychiatrists, anesthesiologists, and physicians working in emergency or primary care although the association is not robust (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In contrast, surgeons and pediatricians have reported lower rates of substance use (7), although this is not a universal finding (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The greater perception of consultant support among psychiatric trainees appears consistent with a recent emphasis on social support at work in UK psychiatry, while the perception of lower family support may reflect more frequent distress in psychiatrists' families due to mental illness, perhaps imposing limitations on how these families support their healthier members 3 . Finally depersonalisation was the only aspect of burnout reduced by the presence of social support, while medical trainees were the only group to benefit from it.…”
Section: Discussionsupporting
confidence: 60%
“…Psychiatrists have reported higher levels of depression 1 misuse of licit and illicit substances 2 , personal or family psychiatric history 3 , and negative personality attributes like neuroticism, agreeableness, and lack of conscientiousness 1 . Studies also suggest that psychiatrists experience higher work-related distress 4 .…”
Section: Introductionmentioning
confidence: 99%